Penerapan Model Contextual Teaching And learning Untuk Meningkatkan Hasil Belajar PAI Pada Siswa kelas IV SDN Bhaktiwinaya 1 - Yuni Kamelia (UNISBA Press, 2024)
Abstract. The purposes of this study are 1) Knowing the objective conditions of PAI learning outcomes after applying the CTL learning method to Islamic Religious Education subjects in fourth grade students at SDN Bhaktiwinaya 1, 2) Implementing the CTL model for fourth grade students at SDN Bhaktiwinaya 1, 3) Knowing the effectiveness the CTL method to improve the learning outcomes of fourth grade students at SDN Bhaktiwinya 1. The research method used in this research is a quantitative approach with a quasi-experimental research method. The results showed that before using the CTL method in the control class IV SD 2 and the experimental class IV SD 2, students tended not to reach the KKM. The average value of the pre-test experimental class was 6 and the average value of the post-test results was 9.8, the student learning outcomes in the experimental class experienced an increase in the average value of 3.8. In the control class the average value of the pre-test results was 5.6 and the average post-test result was 8.2, the learning outcomes of students in the control class experienced an increase in the average value of 2.6. This means that the experimental value is higher than the control class value. Based on the data above, it can be concluded that the Kahoot learning media has an influence on the learning outcomes of fourth grade students in Islamic religious education subjects. This is shown by testing the hypothesis on the t-test (independent sample t-test) on variable x, namely the CTL method and variable y, namely learning outcomes to obtain a Sig value. (2 tailed) 0.000 < 0.005. Abstrak. Tujuan dari penelitian ini yaitu 1) Mengetahui kondisi objektif hasil belajar PAI setelah diterapkan metode pembelajaran CTL pada mata pelajaran Pendidikan Agama Islam pada siswa kelas IV SDN Bhaktiwinaya 1, 2) Melakukan penerapan model CTL terhadap siswa kelas IV SDN Bhaktiwinaya 1, 3)Mengetahui efektivitas metode CTL untuk meningkatkan hasil belajar siswa kelas IV SDN Bhaktiwinya 1. Metode penelitian yang digunakan dalam penelitian ini adalah pendekatan kuantitatif dengan metode penelitian quasi eksperimen. Hasil penelitian menunjukkan bahwa hasil belajar siswa sebelum menggunakan metode CTL pada kelas kontrol IV SD 2 dan kelas eksperimen IV SD 2 cenderung belum mencapai KKM. Nilai rata-rata kelas eksperimen pre-test adalah 6 dan nilai rata-rata hasil post-test adalah 9.8, hasil belajar siswa pada kelas eksperimen mengalami peningkatan nilai rata-rata sebesar 3.8. Pada kelas kontrol nilai rata-rata hasil pre-test adalah 5.6 dan nilai rata-rata hasil post-test adalah 8.2, hasil belajar siswa pada kelas kontrol mengalami peningkata nilai rata-rata sebesar 2.6. Artinya nilai eksperimen lebih tinggi dibandingkan dengan nilai kelas kontrol. Berdasarkan data diatas, dapat disimpulkan bahwa media pembelajaran Kahoot memberikan pengaruh terhadap hasil belajar siswa kelas IV pada mata pelajaran pendidikan agama Islam. Hal ini ditunjukkan dengan uji hipotesis pada uji-t (independent sample t-test) terhadap variable x yaitu metode CTL dan variabel y yaitu hasil belajar memperoleh hasil nilai Sig. (2 tailed) 0.000 < 0.005.